CARICOM/CARIFORUM action plan support and implementation of the CARICOM Single Market and Economy (CSME) : feasibility study (final report) - Corral Fuentes, Jesús Carlos...[et al.] (Global Partners for Economic Development [S.l.], 2005)
Analyzes the current support and needs of CARICOM and its associated organisations for the implementation the CARICOM Single Market and Economy.